Basic Service for Data Collection Evaluation Based on Discrepancy Model in Senior High School - Alamsyah, Muhammad Nur; Hidayah, Nur; Hotifah, Yuliati (PEDAGOGIA, 2024)
This study aims to evaluate the implementation of basic services in the field of data collection in one of the senior high schools in Malang City. The research instruments used were data collection evaluation instruments and interview guidelines and discussions through focus group discussions with bk teachers. The research approach used is mixed method with the type of discrepancy model evaluation research. The data analysis technique applied is descriptive statistical analysis and data triangulation. The results showed that the implementation of data collection services was in the high category, which indicated that the program had run according to the expected standards. However, there are several areas that still require further optimization, especially those related to the evaluation of the implementation process and the assessment of program results. It is recommended that guidance and counseling teachers strengthen their evaluation and assessment practices to ensure continuous improvement of the services provided as well as to demonstrate their effectiveness in meeting students' needs.